Analisis Pemenuhan Kewajiban Perpajakan Pada Perusahaan Media Online, PT. Medira Media Sejahtera (Terasmaluku.Com) Di Kota Ambon - Ann Zusan de Bell (P3M Politeknik Negeri Ambon, 2023)
This study aims to determine the fulfilment of tax obligations of online media companies, PT. Medira Media Sejahtera tax year 2021 based on Law Number 11 of 2020 concerning Job Creation Chapter VI Ease of Doing Business The seventh part of the Taxation Article 111 and Taxes Value Added regulated based on Law Number 11 of 2002 concerning Job Creation Chapter VI Ease of Doing Business The seventh part of The Taxation Article 112. The type of research used is descriptive quantitative research, which refers to the income statement of PT. Medira Media Sejahtera, in 2021. The data sources used in this study are primary data and secondary data. The results showed that in 2021 the company that there are several tax obligations that the company has not fulfilled for corporate taxpayers, which include PPh Article 4 paragraph (2) and PPh Article 17, which is caused by the company's lack of understanding of tax obligations, what the corporate taxpayer must meet. However, in addition to the article mentioned, the company has fulfilled the tax obligations that must be paid. Keywords: Tax, Corporate Taxpayer, Income Tax, Value-added Tax.